Citric Acid as a Feed stimulant - R.S., Balamurali; C.M., Aravindan (Fishery Technology, 2025)
Utility of citric acid as a feed stimulant for fry of Ctenopharyngodon idella was tested. The fry ate more feed containing dry aquatic macrophyte when citric acid was added. Food consumption, feed conversion efficiency and specific growth rate were higher at 0.01 M citric acid concentration.